Partners' Educational Pairings, Work Divisions, and Fertility: Evidence from Germany - Natalie Nitsche (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
The relationship between education and fertility among individuals systematically varies by the education of the partner, according to previous research. For example, couples with two highly educated partners seem to have an accelerated transition to second births, compared to couples with one highly educated partner only, at least in some countries. However, little is known about the underlying mechanisms which may drive this phenomenon. Bringing together the literature on the education-fertility nexus and on associations between men's involvement with domestic work and fertility, this study investigates the role of gendered domestic work divisions for the educational pairing-fertility relationship in couples. Using data from the German Socio-Economic Panel, cox regression, and a cohort approach, findings confirm educational pairing effects; hypergamous couples have higher first birth rates in the birth cohorts 1950-1965 and 1966-75, while highly educated homogamous couples display the highest second birth rates in all examined birth cohorts (1950-65, 1966-75, 1976-85). While educational pairing effects for first births are largely mediated by paid and unpaid work divisions, this is not the case for second births. Here, positive effects of increases in his time spent with housework are independent of the educational pairing effect, warranting future exploration into additional mechanisms.
Keywords: 300; Couples; fertility; education; housework; child care; Germany